O planejamento como orientador da organização do ensino de matemática - Kronbauer, Cíntia Fogliatto (2022)
This doctoral research, linked to the Graduate Program in Education at the Federal University of Santa Maria (PPGE/UFSM), in line with the research line “Teaching, knowledge and professional development” linked to investigative actions the Group of Studies and Research in Mathematics Education - GEPEMat, investigates the process of teaching activity of Mathematics that can emerge during a continuous training activity with teachers who teach and will teach Mathematics. This research implies understanding the relationships of our research object, the teaching organization, materialized in its particular sense: planning. In the direction of the guiding dimension we have the general objective is: To understand how the Actions that are part of the organized planning within the scope of a Shared Training Space constitute themselves as guides in the teaching organization, leading to the teaching activity. The approach to the research object occurred through an Extension Course Seven teachers and future teachers participated in the same, and the training meetings took place remotely via the Google Meet platform. The investigative instruments were: audio and video recordings of meetings and a questionnaire, totaling 19 meetings that took place fortnightly, synchronously, throughout the year 2020. The thesis to be defended is that when the planning is elaborated collectively, intentionally, and shared between different subjects that make up a training space, they attribute meanings that coincide with the social meaning. The Actions that compose it become a Guiding teaching organization, and planning constitutes an element in the process of teaching activity. The analysis is related to the theoretical-methodological principles of the Historical-Cultural Theory and the Activity Theory based on contributions, mainly from Vigostki (1896-1934) and Leontiev (1903-1979) and other authors based on this study perspective. From the results, we evidence five actions that are part of the planning and that constitute guides of the teaching organization: Guiding Action 1: Approaching the educational context, Guiding Action 2: Studying the Logical-Historical Movement of the Concept, Guiding Action 3: Develop the lesson plan, Guiding Action 4: Develop the lesson plan and Guiding Action 5: Evaluate the planning process. The action analysis can reveal evidence of meanings attributed by teachers to the Actions constitutive of planning that guides the organization of Mathematics teaching. In turn, the meaningful process triggers through meanings that participants attribute to the Actions in the planning activity. Therefore, planning becomes a meaningful element for teaching activity when it elaborates in a shared, intentional, and collective way in a training space organized for this purpose. Thus, an EFC structured on theoretical-methodological principles of THC is a potentiator in the training process for subjects who participate in it.